2001
DOI: 10.1002/bip.10000
|View full text |Cite
|
Sign up to set email alerts
|

Homonuclear 1H‐NMR assignment and structural characterization of human immunodeficiency virus type 1 Tat Mal protein

Abstract: The transacting transcriptional activator (Tat) is a viral protein essential for activation of the human immunodeficiency virus (HIV) genes, and it plays an important role in HIV induced immunodeficiency. We report the NMR structural characterization of the active Tat Mal variant that belongs to a highly virulent D-subtype HIV type-1 (HIV-1) strain (Mal) found mainly in Africa. A full Tat Mal protein (87 residues) is synthesized. This synthetic protein is active in a transactivation assay with HeLa cells infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 23 publications
7
56
2
Order By: Relevance
“…The low intensity of the negative bands at 200 nm suggests that the three proteins are not random-coil but rather structured with ␤-turns as the main secondary structures. This is in agreement with the Tat Mal structure determined by two-dimensional NMR (19). Tat Ug05RP and Tat Mal have similar CD spectra, whereas differences are observed in the CD spectrum of Tat Ug11LTS (Fig.…”
Section: Ug05rp Induces Greater Up-regulation Of Fasl Mrna Compared Wsupporting
confidence: 89%
See 4 more Smart Citations
“…The low intensity of the negative bands at 200 nm suggests that the three proteins are not random-coil but rather structured with ␤-turns as the main secondary structures. This is in agreement with the Tat Mal structure determined by two-dimensional NMR (19). Tat Ug05RP and Tat Mal have similar CD spectra, whereas differences are observed in the CD spectrum of Tat Ug11LTS (Fig.…”
Section: Ug05rp Induces Greater Up-regulation Of Fasl Mrna Compared Wsupporting
confidence: 89%
“…Interestingly, we found that there is just 5% ␣-helix structure (three to four residues) in both Tat Mal and Tal Ug05RP, but not in Tat Ug11LTS. Molecular modeling of Ug05RP using the NMR structure of Tat Mal (19) showed that it is possible to obtain a structure similar to that of Tat Mal despite the mutations in these two proteins, in agreement with the CD spectra (Fig. 5).…”
Section: Ug05rp Induces Greater Up-regulation Of Fasl Mrna Compared Wsupporting
confidence: 73%
See 3 more Smart Citations